SELECTING PROPOSITION OF METHODS TO STUDY ECONOMIC VALUATION OF MARINE ECOSYSTEMS IN VIETNAM - Lan, Tran Dinh; Huyen, Nguyen Thi Minh; Dung, Le Quang; Thu, Nguyen Thi (Vietnam Journal of Marine Science and Technology, 2014)
Three basic approaches in resources valuation have been applied worldwide as well as initially used in Vietnam generally and in marine ecosystems particularly, including Impact Analysis Valuation, Partial Valuation and Total Economic Valuation. However, studying results in Vietnam are still limited and not taken into account all ecosystem values. Recent studies on marine and coastal resources valuation in Vietnam show the possibility to approach and apply several methods in identification and valuation of ecosystem values, particularly indirect and non-use values. This is a combined system of the methods for marine ecology and natural resources as well as the methods for ecological and environmental valuation.